Cutaneous malignancies in patients with Parkinson’s disease at a dermato-oncological university centre in Hungary - Tóth, Veronika; Diakoumakou, Stefani Christina; Kuroli, Enikő; Tóth, Béla; Kuzmanovszki, Daniella; Szakonyi, József; Lőrincz, Kende Kálmán; Somlai, Beáta; Kárpáti, Sarolta; Holló, Péter (Frontiers in Oncology, 2023)
(1) Background: The possible correlation between melanoma and Parkinson’s disease (PD) has been intensively studied. In this work, we aimed to assess the coincidence of skin malignancies and PD at a dermato-oncological university centre in Central-Eastern Europe, Hungary. (2) Methods: From 2004 to 2017, a retrospective analysis of the centre's database was performed based on International Statistical Classification of Diseases-10 codes. (3) Results: Out of the patients who visited the clinic during the study period, 20,658 were treated for malignant skin tumours. Over the 14 years, 205 dermatological patients had PD simultaneously, 111 (54%) of whom had at least one type of skin malignancy: melanoma (n=22), basal cell carcinoma (BCC) (n=82) or squamous cell carcinoma (SCC) (n=36) (in some patients, multiple skin tumours were identified). Compared to the age- and sex-matched control group, patients with PD had a significantly lower risk for basal cell carcinoma (OR: 0.65, 95% CI: 0.47-0.89, p=0.0076) and for all skin tumours (OR: 0.74, 95% CI: 0.56-0.98, p=0.0392) but not for melanoma. (4) Conclusions: We found a decreased risk of all skin tumours and basal cell carcinoma and an unchanged risk of melanoma among patients with PD. However, it should be kept in mind that some large-scale meta-analyses suggest a higher incidence of melanoma after a diagnosis of PD, indicating the importance of skin examination in this vulnerable population.